The role of surgery in older patients with T1-2N0M0 small cell lung cancer: A propensity score matching analysis - Ning, Jing; Ge, Tao; Zhu, Shuncang; Han, Yingli; Ruan, Suhong; Ma, Yuchen; Liu, Rentao (Frontiers in Oncology, 2022)
Background Surgical resection could improve the survival of patients with early-stage small cell lung cancer (SCLC). However, there is a lack of dedicated studies concentrating on surgical treatment in older patients with T1-2N0M0 SCLC. Thus, we performed this population-based study to investigate whether older patients with T1-2N0M0 SCLC could benefit from surgery. Methods We collected the data of patients with SCLC between 2000 and 2015 from the Surveillance, Epidemiology, and End Results Program database. Older patients (≥ 65 years) with T1-2N0M0 SCLC were included, and we converted the staging information into those of the eighth edition. The propensity score matching (PSM) was used to balance the distribution of clinical characteristics between surgery and no-surgery groups. Results Before PSM, the distribution proportions of clinical characteristics in 1,229 patients were unbalanced. The Kaplan–Meier curves of overall survival (OS) and cancer-specific survival (CSS) showed that the patients in the surgery group were better than those in the non-surgery group (all P < 0.001). After 1:2 PSM, the distribution proportions of clinical characteristics in 683 patients were balanced (all P > 0.05). The OS and CSS of patients in the surgery group were still better than that of patients in the no-surgery group (all P < 0.001), and subgroup analysis showed that the surgery was a protective factor for OS and CSS in all clinical characteristics subgroups (almost P < 0.001). The multivariate Cox analysis further confirmed this result (OS: HR, 0.33; 95% CI, 0.27–0.39; P < 0.001; CSS: HR, 0.29; 95% CI, 0.23–0.36; P < 0.001). The result of subgroup analysis based on age, T stage, and adjuvant therapy showed that surgery was related to better OS and CSS compared with non-surgery group (almost P < 0.001) and that lobectomy exhibited the longer survival than sublobectomy. Age, sex, and race were the independent prognostic factors for OS in patients undergoing surgery, whereas only the factor of age affects the CSS in patients with surgery. Conclusions Older patients with T1-2N0M0 SCLC can benefit significantly from surgical treatment, and lobectomy provides better prognosis than sublobectomy.